A Retrospective Evaluation of the Frequency of Impulsive Compulsive Behaviors in Parkinson's Disease Patients Treated with Continuous Waking Day Apomorphine Pumps. Issue 3 (11th August 2016) - Barbosa, Pedro; Lees, Andrew J.; Magee, Cathy; Djamshidian, Atbin; Warner, Thomas T.
Abstract: Background: Impulsive compulsive behaviors (ICBs) can have a deleterious impact on the lives of patients with PD with orally active dopamine agonist treatment recognized as the greatest risk factor. However, the relationship between subcutaneous administration of the dopamine agonist, apomorphine, and impulsive compulsive behaviors is unknown. Methods: We conducted a retrospective analysis of 28 advanced PD patients treated with subcutaneous waking day apomorphine ambulatory minipumps at the National Hospital for Neurology and Neurosurgery (London, UK). Results: Twelve of the patients had experienced impulsive compulsive behaviors before starting apomorphine. Reduction of oral dopamine agonist dose before apomorphine had led to complete resolution in 6 cases with no recurrence on long‐term apomorphine maintenance therapy. Six patients still had active impulsive compulsive behaviors when apomorphine was started. Four of these improved, and in the other 2 there was no worsening. Of the 16 patients with no previous history of impulsive compulsive behaviors who started apomorphine, only 1, who was still receiving concurrent levodopa, developed impulsive compulsive behaviors. Conclusions: These data provide preliminary evidence that continuous apomorphine pump therapy has a lower proclivity to trigger or exacerbate impulsive compulsive behaviors than oral dopamine agonists. This is likely to be attributed to a more tonic stimulation of striatal dopamine receptors leading to desensitisation, but could also be attributed to a different pharmacological profile of apomorphine compared with orally active dopamine agonists. Apomorphine can be considered as a treatment option in patients who have developed disabling impulsive compulsive behaviors on oral agonist therapy whose motor handicap cannot be controlled adequately onl ‐dopa alone. Further prospective studies are needed to provide a definitive answer to this question.